براہوئی ڈرامہ نا اولیکو کتاب ’’استو نا بندغ‘‘ اسہ جاچ اس: Brahui Drama Naa Avleeko Kitaab :Isto Naa Bandagh: asi Jaach ass - Muhammad Ashraf; Kiazai, Muhammad Nasir (Al-Burz, 2019)
Raag, a folk term has used for Drama in ancient Brahui. In folk literature when the Brahui modern literature were not introduced the Term Raag were used for entertain. After establishment of Radio Station center at Quetta, the different parts of modern literature opened the windows for Brahui fiction. There is prominent writer which Mr. Ghulam Nabi Rahi has started firstly Brahui radio Drama, soon after the tradition of Brahui drama has spread all over the Balochistan. A compilation of his first period’s Drama known as Isto naa Bandagh. This research paper discussed and analyses the technique and tendency of Rahi’s Drama. Mostly his dramas have played from Radio and Television Quetta center after Sixties. Shaahbeg naa wataakh a very famous radio Drama, where the social problems were reflecting. A descriptive method has been used to complete this paper.